2011
DOI: 10.1371/journal.pmed.1001108
|View full text |Cite
|
Sign up to set email alerts
|

Educating a New Generation of Doctors to Improve the Health of Populations in Low- and Middle-Income Countries

Abstract: Francesca Celletti and colleagues from WHO argue that a transformation in the scale-up of medical education in low- and middle-income countries is needed, and detail what this might look like.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 17 publications
1
60
0
3
Order By: Relevance
“…[15][16][17] Regardless, the demand for improved prehospital and hospitalbased EM specialty training in this country continues to grow. [18] Despite previous successes of SGL medical education in Tanzania, there have been few investigations of SGL acceptability in the region, and none for EM education. A recent study showed significant improvement to trauma resuscitation knowledge following implementation of a small-group-based resuscitation simulation course, [19] but researchers have yet to investigate the impact of SGL on other topics within the scope of EM postgraduate training.…”
Section: Emergency Medicine In Tanzaniamentioning
confidence: 99%
“…[15][16][17] Regardless, the demand for improved prehospital and hospitalbased EM specialty training in this country continues to grow. [18] Despite previous successes of SGL medical education in Tanzania, there have been few investigations of SGL acceptability in the region, and none for EM education. A recent study showed significant improvement to trauma resuscitation knowledge following implementation of a small-group-based resuscitation simulation course, [19] but researchers have yet to investigate the impact of SGL on other topics within the scope of EM postgraduate training.…”
Section: Emergency Medicine In Tanzaniamentioning
confidence: 99%
“…A transformative scaling up of health professional preparation is imperative to the improvement of population health outcomes in Sudan, similar to other low-and middle-income countries. Critical elements of transformative education include a clear strategy or framework, and effective and relatable health sciences education to increase-not just the quantity-but also the quality and relevance of health-care professionals (Celletti et al, 2011;World Health Organization, 2013). This necessitates context-relevant curricula developed and revised by local faculty.…”
Section: Background and Rationalmentioning
confidence: 99%
“…Our search did not find studies calculating the rates of return to any type of health professional training in low-income countries, though some recent qualitative work suggests that rates of return may be limited by shortcomings in training institutions (Celletti et al 2011;Ferrinho et al 2011). Examining how changes in wages influence hours worked and labor force participation is a central concern of labor economics .…”
Section: Education Training and Specialty Choicementioning
confidence: 99%